Diseño de un modelo de gestión del conocimiento para la empresa Interconst Ingenieria SAS (2021)
INTERCONST INGENIERIA SAS is a micro-company whose main corporate purpose is the execution of construction, supervision, audit, design and consulting projects for civil and architectural works, located in the municipality of Gigante - Huila. It has had good results in the 2 years it has been in office, due to the development of 8 contracts with Constructora Rodríguez Briñez SAS, 2 contracts with Construespacios SAS and 1 contract with Consorcio Huila 2017, effectively carried out with adequate results regarding the contracted services. It generates 5 direct jobs and 1 indirect within the department of Huila. Currently, INTERCONST INGENIERIA SAS does not have a knowledge management model, so implementing it will allow it to manage resources more efficiently and generate improvements in its processes that allow economic and commercial growth.